Effect of combined V and Ti microalloying on the microstructure and mechanical properties of TRIP-aided bainitic ferrite steel during industrial continuous annealing - Zhixiang Liu; Xiao Hu; Tao Xie; Haoqing Zheng; Guanqiao Su; Yang Jin; Hua Fan; Hui Wang; Xuefei Huang (Journal of Materials Research and Technology)
The industrial production of carbide-free bainitic steels (i.e., TRIP-aided bainitic ferrite steels) plays a crucial role in achieving automotive lightweighting. This study focuses on the isothermal transformation kinetics, microstructural evolution, and mechanical properties of a low-carbon carbide-free bainitic steel heat-treated by a typical industrial continuous annealing (ICA) process. And the effects of the combined addition of 0.1 wt% V and Ti on these aspects were systematically investigated. The results show that a significant refinement of the prior austenite grain (PAG) size (from 15.8 μm to 3.4 μm) was achieved due to the co-addition of V and Ti. This grain refinement induced a chain of subsequent effects. On the positive side, the reduction in prior austenite grain (PAG) size promoted the refinement of martensite/austenite (M/A) constituents as well as both blocky and film-like retained austenite (RA) in the VTi-added steel. Unfortunately, the smaller PAGs also led to the coarsening of bainitic laths and the appearance of granular bainite. Consequently, compared to the VTi-free steel, the VTi-added steel exhibited slightly lower yield strength and ultimate tensile strength (961 MPa and 1199 MPa, respectively), but a higher elongation (12.8 %). Analysis of the bainitic transformation kinetics revealed that the combined addition of V and Ti accelerated the early-stage transformation due to enhanced nucleation, but retarded the later-stage transformation owing to inhibited growth. According to the findings of this study, although co-microalloying with V and Ti effectively refines PAGs and facilitates precipitation strengthening, excessively fine PAGs are detrimental to the formation of a high-strength lath bainite microstructure. Therefore, in industrial production, the addition amounts of V and Ti should be carefully optimized to ensure an appropriate grain refinement.